Social Science Learning through Google Sites and Smart Box in Junior High Schools - Fadhil Akbar; Imam Suprayogo; M. Fahim Tharaba; Bima Fandi Asy’arie; Mariyana, Weni (Universitas Pendidikan Ganesha, 2024)
Social studies teachers need to use the correct method approach. Learning activities also do not utilize technology, so students need help learning. Based on this, this study aims to develop social studies learning through Google sites and bright boxes as learning media. This study uses the research and development (R&D) type, using the ADDIE development model. The study subjects were material experts, learning design experts, and learning media experts. The subjects of the trial study were 33 students of SMP Negeri 12 Malang. The methods used to collect data were interviews, questionnaires, observations, tests, and documentation. The instruments used to collect data were questionnaire sheets and test questions. The techniques used to analyze the data were qualitative and quantitative descriptive analysis. The study's results showed that, First, the design of social studies learning development products through supporting applications such as (Canva, Capcut, Wordwall, and Google Sites). The assessment of the material expert validator was 83.0%. The evaluation of the learning design expert validator was 83.0%. The assessment of the learning media expert validator was 83.3%. Third, the practicality of the design of the IPS learning product after being implemented in students obtained the highest value of 62.0%, with the category of Very Appropriate. The teacher's response received a percentage of 4.7%, Very Practical. It was concluded that developing IPS learning through Google Sites and Smart Boxes was proven very effective and running optimally. This research implies that social studies learning through google sites and smart boxes can be used to help students learn.